Total Quality: Asking Critical Questions - Wilkinson, Adrian; Willmott, Hugh (Academy of Management Review, 1995)
The article presents a response to a 1995 special issue of “Academy of Management Review” focusing on total quality management (TQM). In reviewing the contributions to that earlier issue, the author's suggest some further areas of TQM research based on their European experience. The authors claim that the exploration within that issue falls short of discussing how TQM promotes a higher quality of life. Instead, the scholarship focuses on the implementation of TQM within the organization. The authors stress that TQM's benefits to employees and their own sense of empowerment is worthy of exploration.